CD34 evaluation of microvasculature in lung adenocarcinoma and its microvascular density predicts postoperative tumor recurrence - Zijian Qiu; Jiaji Wu; Guanchao Pang; Xia Xu; Jun Lin; Pingli Wang (Pathology and Oncology Research)
BackgroundAngiogenesis is closely associated with tumor growth and metastasis, and microvascular density (MVD) is currently the clinical standard for evaluating tumor angiogenesis. Thus, the detection of intratumoral MVD is of great significance for understanding disease progression and predicting patient prognosis.MethodsTumor tissue sections of 238 patients with lung adenocarcinoma (LUAD) who underwent radical surgery were retrospectively analyzed. Immunohistochemical (IHC) staining was carried out using a CD34 polyclonal antibody to determine intratumoral MVD, and the relationship of CD34-MVD with the clinicopathological characteristics and survival time of LUAD patients was analyzed.ResultsCD34-MVD was associated with tumor size, lymph node metastasis, tumor recurrence, and patient survival status; patients with tumor size ≤3 cm (P = 0.015), negative for lymph node metastasis (P = 0.049), no tumor recurrence (P = 0.021), and survival (P = 0.042) had higher MVD. Survival analysis suggested that patients with high MVD had higher disease-free survival (log-rank P = 0.005) and overall survival (log-rank P = 0.004) compared to patients with low MVD. The Cox proportional hazards model showed that a high MVD (P = 0.022) reduced the risk of postoperative tumor recurrence in patients with LUAD.ConclusionDecreased intratumoral CD34 positive microvessels were associated with tumor development in patients with LUAD. CD34-MVD is an independent risk factor affecting postoperative tumor recurrence in patients with LUAD and can be used as a prognostic indicator for this group of patients.